Growth hormone resistance exacerbates cholestasis‐induced murine liver fibrosis. Issue 2 (February 2015) - Stiedl, Patricia; McMahon, Robert; Blaas, Leander; Stanek, Victoria; Svinka, Jasmin; Grabner, Beatrice; Zollner, Gernot; Kessler, Sonja M.; Claudel, Thierry; Müller, Mathias; Mikulits, Wolfgang; Bilban, Martin; et al.
<x xml:space="preserve">Abstract</x> Growth hormone (GH) resistance has been associated with liver cirrhosis in humans but its contribution to the disease remains controversial. In order to elucidate whether GH resistance plays a causal role in the establishment and development of liver fibrosis, or rather represents a major consequence thereof, we challenged mice lacking the GH receptor gene (Ghr–/–, a model for GH resistance) by crossing them with Mdr2 knockout mice (Mdr2–/–), a mouse model of inflammatory cholestasis and liver fibrosis. Ghr–/–;Mdr2–/– mice showed elevated serum markers associated with liver damage and cholestasis, extensive bile duct proliferation, and increased collagen deposition relative to Mdr2–/– mice, thus suggesting a more severe liver fibrosis phenotype. Additionally, Ghr–/–;Mdr2–/– mice had a pronounced down‐regulation of hepatoprotective genes Hnf6, Egfr, and Igf‐1, and significantly increased levels of reactive oxygen species (ROS) and apoptosis in hepatocytes, compared to control mice. Moreover, single knockout mice (Ghr–/–) fed with a diet containing 1% cholic acid displayed an increase in hepatocyte ROS production, hepatocyte apoptosis, and bile infarcts compared to their wild‐type littermates, indicating that loss of Ghr renders hepatocytes more susceptible to toxic bile acid accumulation. Surprisingly, and despite their severe fibrotic phenotype, Ghr–/–;Mdr2–/– mice displayed a significant decrease in tumor incidence compared to Mdr2–/– mice, indicating that loss of Ghr signaling may slow the progression from fibrosis/cirrhosis to cancer in the liver. Conclusion: GH resistance dramatically exacerbates liver fibrosis in a mouse model of inflammatory cholestasis, therefore suggesting that GH resistance plays a causal role in the disease and provides a novel target for the development of liver fibrosis treatments. (Hepatology 2015;61:613‐626)